Oscillation and Nonoscillatory Criteria of Higher Order Dynamic Equations on Time Scales - Ya-Ru Zhu; Zhong-Xuan Mao; Jing-Feng Tian; Ya-Gang Zhang; Xin-Ni Lin (Mathematics, 2022)
In this paper, we consider two universal higher order dynamic equations with several delay functions. We will establish two oscillatory criteria of the first equation and a sufficient and necessary condition for the second equation with a nonoscillatory solution by employing fixed point theorem.